1996
DOI: 10.1152/ajpregu.1996.271.6.r1529
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular remodeling during development and recovery from modified tachycardia-induced cardiomyopathy model

Abstract: This study was designed to characterize left ventricular (LV) function and mass in a modified cardiomyopathy model in the dog in which right ventricular pacing rates are gradually increased throughout 38 days. On the last day of the pacing protocol, ejection fraction was reduced (25 +/- 3 vs. 60 +/- 1%) and LV end-diastolic diameter index (a ratio of LV end-diastolic diameter to body weight, 2.09 +/- 0.02 vs. 1.79 +/- 0.08 mm/kg) and LV mass index (a ratio of LV mass to body weight, 5.2 +/- 0.3 vs. 4.3 +/- 0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…An early study reported that patients with a PVC burden of 20 % were more likely to have impaired LV function compared with those patients with a PVC burden of <20 %. 76 A later study found that a PVC burden of 16 % by a receiver operating characteristic (ROC) curve analysis best separated patients with and without TIC. 109 Most recently, a PVC burden of 24 % was reported to be strongly associated with the presence of cardiomyopathy, although this cut-off value failed to identify every individual at risk of cardiomyopathy and the critical burden for some patients was noted to be lower.…”
Section: Ventricular Tachycardiamentioning
confidence: 99%
See 1 more Smart Citation
“…An early study reported that patients with a PVC burden of 20 % were more likely to have impaired LV function compared with those patients with a PVC burden of <20 %. 76 A later study found that a PVC burden of 16 % by a receiver operating characteristic (ROC) curve analysis best separated patients with and without TIC. 109 Most recently, a PVC burden of 24 % was reported to be strongly associated with the presence of cardiomyopathy, although this cut-off value failed to identify every individual at risk of cardiomyopathy and the critical burden for some patients was noted to be lower.…”
Section: Ventricular Tachycardiamentioning
confidence: 99%
“…33,38,40,50 Changes in intracardiac filling pressures, cardiac output and systemic vascular resistance are generally reversible with cessation of rapid pacing, although in some cases ejection fraction may not return to baseline and abnormalities in contractile function may persist. 33,76 Within 48 hours of cessation of pacing, intracardiac filling pressures, systemic arterial pressures, systemic vascular resistance and cardiac index have been shown to return to levels similar to control animals. 34 Significant improvements in LVEF have been shown by 24-48 hours with normalisation after 1-2 weeks.…”
Section: Time Course and Recoverymentioning
confidence: 99%
“…6 After a 2-week recovery period, the pacemaker was programmed to 180 bpm for 10 days, after which the pacing rate was increased at 7-day intervals sequentially to 200, 210, 220, and 240 bpm as previously described. 6,7 …”
Section: Hf Modelmentioning
confidence: 99%
“…TRCM is associated with marked left ventricular (LV) dilatation, systolic dysfunction, and disruption of the fibrillar collagen network. [1][2][3][4][5][6][7] Further, reduced myocyte adhesion to constituents of the basement membrane 4,8 has been reported in TRCM and may contribute to myocyte elongation, chamber remodeling, dysfunction, and altered mechanotransduction because of the decreased coupling of the myocyte sarcolemma to the extracellular matrix (ECM).…”
mentioning
confidence: 99%
“…In some publications, left ventricular ejection fraction (LVEF) reduced up to 24-28% and moderate to severe MR was developed after rapid pacing 77,78,80 . One drawback of this model is that after recovery from rapid pacing, LV function return to levels seen in the healthy animals 81 . In light of this observation, researchers should pay attention to this fact with regard to evaluation of device efficacy.…”
Section: Mitral Valve Repairmentioning
confidence: 99%